Weaving Science Communication Training through an Undergraduate Science Program with a Focus on Accessibility and Inclusion - Adina Silver; Zoya Adeel; Tim Li; Abeer Siddiqui; Alexander Hall; Sarah L Symons; Katie Moisse (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Science communication training can help scientists engage diverse audiences with the promise and process of science, helping to strengthen science literacy and preserve public trust in science. But not all scientists have access to such training. To address this shortfall, we have embedded a suite of science communication courses in the Life Sciences Program, the largest undergraduate science program at McMaster University in Hamilton, Ontario. A foundational course focuses on making science accessible through inclusive language and media, while more advanced courses emphasize the importance of understanding and centering the values, beliefs, questions, and critiques of audiences, and using narratives and rhetoric to inform, inspire, and ignite change. Throughout the curriculum, students engage with and contribute to the scholarship of science communication. They graduate with skills that serve them in diverse careers. In this article, we outline the structure of our curriculum and detail key components of our science communication courses. We also describe a student-led assessment of our curriculum that highlights strengths and opportunities for improvement. Ultimately, we strive to provide a compelling rationale for teaching science communication at the undergraduate level by sharing a framework of replicable pedagogical practices for engaging large cohorts of students with both the theory and practice of science communication.